How to moderate emotional exhaustion among public healthcare professionals? - M. Ángeles López-Cabarcos; Analía López-Carballeira; Carlos Ferro-Soto (European Research on Management and Business Economics (ERMBE), 2021)
This paper analyzes the mediating role of employees' emotional exhaustion between laissez-faire leadership and employees' job attitudes (intrinsic satisfaction and turnover intention), and also the moderating role of influence at work, interactional justice and helping behaviors on employees' feelings of emotional exhaustion. Structural equation modeling and multigroup analysis were used in a sample of 511 public healthcare professionals. The results show that emotional exhaustion partially mediates the relationships between laissez-faire leadership and both intrinsic satisfaction and turnover intention. Influence at work moderates the relationship between laissez-faire leadership and emotional exhaustion; interactional justice moderates the relationship between emotional exhaustion and intrinsic satisfaction; and extra-role behaviors moderate the relationship between emotional exhaustion and turnover intention. To date, there are few studies analyzing the mediating role of emotional exhaustion in public healthcare, and there are no studies analyzing how its negative effects can be moderated. The conclusions may help human resources managers design new strategies to prevent and mitigate emotional exhaustion and contribute healthcare employees to cope with its serious effects, encouraging a healthy environment that gives priority to workers' well-being and service quality.
Keywords: M12; M54; 650; Emotional exhaustion; Laissez-faire leadership; Intrinsic satisfaction; Turnover intention